2020
DOI: 10.1093/jxb/eraa024
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium–silicon interactions in higher plants: an update

Abstract: Aluminium (Al) and silicon (Si) are abundant in soils, but their availability for plant uptake is limited by low solubility. However, Al toxicity is a major problem in naturally occurring acid soils and in soils affected by acidic precipitation. When, in 1995, we reviewed this topic for the Journal of Experimental Botany, it was clear that under certain circumstances soluble Si could ameliorate the toxic effects of Al, an effect mirrored in organisms beyond the plant kingdom. In the 25 years since our review, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 94 publications
(83 reference statements)
1
33
0
Order By: Relevance
“…Numerous studies, have shown that Si supply affects aluminum (Al) uptake, and subsequently plant tolerance to Al-toxicity, by either external ( ex planta ) and/or internal ( in planta ) mechanisms (see Hodson and Evans, 2020 and reference therein). Early investigations showed that the ameliorative effect of Si on Al toxicity could mainly be attributed to increased pH of the rhizosphere.…”
Section: Interactions Of Silicon With Beneficial Elementsmentioning
confidence: 99%
See 4 more Smart Citations
“…Numerous studies, have shown that Si supply affects aluminum (Al) uptake, and subsequently plant tolerance to Al-toxicity, by either external ( ex planta ) and/or internal ( in planta ) mechanisms (see Hodson and Evans, 2020 and reference therein). Early investigations showed that the ameliorative effect of Si on Al toxicity could mainly be attributed to increased pH of the rhizosphere.…”
Section: Interactions Of Silicon With Beneficial Elementsmentioning
confidence: 99%
“…From chemical studies on Al-Si interaction in solution it was also known that pH influenced the formation of sub-colloidal inert hydroxyaluminosilicate species (HAS) ( Exley and Birchall, 1992 , 1993 ). However, the potential impact of HAS on plant growth was not appreciated until Baylis et al (1994) reported that at low pH, a higher concentration Si was required to ameliorate Al toxicity by soybean; the authors postulated that basis for this higher demand for Si was the higher affinity of Si for Al in HAS formation at low pH (see Hodson and Evans, 2020 ). The beneficial effect of silicic acid was also confirmed in later studies on Al-Si interaction in maize ( Ma et al, 1997 ).…”
Section: Interactions Of Silicon With Beneficial Elementsmentioning
confidence: 99%
See 3 more Smart Citations